Foreign body and caustic ingestions in children: A clinical practice guideline. Issue 11 (November 2020) - Oliva, Salvatore; Romano, Claudio; De Angelis, Paola; Isoldi, Sara; Mantegazza, Cecilia; Felici, Enrico; Dabizzi, Emanuele; Fava, Giorgio; Renzo, Sara; Strisciuglio, Caterina; Quitadamo, Paolo; Saccomani, Marco Deganello; et al.
ABSTRACT: Foreign body and caustic ingestions in children are usually the most common clinical challenges for emergency physicians, general pediatricians and pediatric gastroenterologists. Management of these conditions often requires different levels of expertise and competence. Endoscopy is often necessary but there is a high risk of misusing this tool with incorrect timing and indications. The imprecise clinical history frequently leaves clinicians uncertain about timing and nature of the ingestion. Few clinical guidelines regarding management of these ingestions in children have been published, none of which from the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP). An expert panel of Italian endoscopists was convened by the SIGENP Endoscopy Working Group to produce the present article that outlines practical clinical approaches to the pediatric patient with a variety of foreign body and caustic ingestions. The Italian Association of Hospital Gastroenterologists and Endoscopists (AIGO) has also endorsed the project since many adult endoscopists usually manage children with these conditions. Differently from the other published guidelines, the proposed one focuses on the role of the endoscopists (regardless of whether they are adult or pediatric gastroenterologists) in the diagnostic process of children with foreign body and caustic ingestions.